2021
DOI: 10.1016/j.cmi.2020.03.018
|View full text |Cite
|
Sign up to set email alerts
|

FAM19A4/miR124-2 methylation analysis as a triage test for HPV-positive women: cross-sectional and longitudinal data from a Dutch screening cohort

Abstract: Objectives: The aim was to evaluate the cross-sectional and long-term triage performance of FAM19A4/ miR124-2 methylation analysis in human papillomavirus (HPV)-based cervical screening. Methods: We conducted a post hoc analysis within a Dutch population-based HPV-positive study cohort of women aged 30e60 years (n ¼ 979). Cross-sectional cervical intraepithelial neoplasia (CIN) 3þ sensitivity, specificity, positive predictive value and negative predictive value as well as cumulative CIN3þ or cervical cancer ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 29 publications
3
39
0
Order By: Relevance
“…Long‐term follow‐up data from a Dutch cervical screening cohort showed that the cervical cancer risk among hrHPV‐positive women after 14 years is lower following a negative FAM19A4/miR124‐2 methylation result compared with a negative cytology result and that the CIN3+ risk is similar following a negative methylation or cytology result 26,69 . This lower long‐term CIN3+ risk after a negative FAM19A4/miR124‐2 methylation test was confirmed in another study from the Netherlands 70 …”
Section: Use Of Methylation Analysis In Cervical Screeningmentioning
confidence: 69%
See 1 more Smart Citation
“…Long‐term follow‐up data from a Dutch cervical screening cohort showed that the cervical cancer risk among hrHPV‐positive women after 14 years is lower following a negative FAM19A4/miR124‐2 methylation result compared with a negative cytology result and that the CIN3+ risk is similar following a negative methylation or cytology result 26,69 . This lower long‐term CIN3+ risk after a negative FAM19A4/miR124‐2 methylation test was confirmed in another study from the Netherlands 70 …”
Section: Use Of Methylation Analysis In Cervical Screeningmentioning
confidence: 69%
“…26,69 This lower long-term CIN3+ risk after a negative FAM19A4/miR124-2 methylation test was confirmed in another study from the Netherlands. 70 Secondary triage for CIN3 or worse of women with ASC-US/LSIL cytology Current HPV-based cervical screening programmes often use cytology for triage of hrHPV-positive women, referring all women with abnormal cytology (≥atypical squamous cells of unknown significance [ASC-US]) at baseline or after 6 months for colposcopy. Although this triage strategy significantly improves the specificity of the primary hrHPV test, over-referral of women without clinically relevant lesions remains an issue, particularly among young women with low-grade cytological abnormalities (ASC-US or lowgrade squamous intraepithelial lesion [LSIL]).…”
Section: Cross-sectional Performance Of Methylation Markers For Primary Triage Of Hrhpv-positive Womenmentioning
confidence: 99%
“…Samples that were either GP5+/6 + PCR-EIA positive and/or HC2 positive, but negative on RLB for HPV type 16, 18, 31, 33 and 45 were considered negative for HPV16/18/31/33/45. FAM19A4/miR124-2 methylation analysis was performed as described previously [30,31], blinded for cytology and histology outcomes, by quantitative methylation specific PCR (qMSP) on bisulphite converted DNA from cervical scrapes using the QIAsure Methylation Test® (Qiagen, Hilden, Germany) (VUSA-Screen cohort) or its prototype version (POBASCAM cohort). This prototype version was identical regarding to the primers and probes design, PCR conditions and PCR system.…”
Section: Study Populationmentioning
confidence: 99%
“…Although this algorithm might be less cost‐effective in a short‐term, a fast time‐response for high‐grade lesions and the reduction of unnecessary medical procedures will increase cost‐effectiveness of the screening program. Moreover, methylation as triage test identified risk for CIN3+ or cervical cancer similar to cytology and HPV genotyping in longitudinal studies, with the major advantage of allowing for assessment in self‐collected samples 33,46,47 . Nonetheless, it should be acknowledged that different strategies might be adopted in other regions/countries, aiming at increased colposcopy referral and cervical cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…+ or cervical cancer similar to cytology and HPV genotyping in longitudinal studies, with the major advantage of allowing for assessment in self-collected samples. 33,46,47 Nonetheless, it should be acknowledged that different strategies might be adopted in other regions/ countries, aiming at increased colposcopy referral and cervical cancer diagnosis. In these situations, methylation-based triage might be less cost-effective than extended genotyping and cytology.…”
Section: Discussionmentioning
confidence: 99%